Revealed and concealed preferences in the Chilean pension system: an experimental investigation - Barr, A; Packard, T (University of Oxford, 2000)
Using survey data and a field experiment to measure agents' risk and time preferences, we identify the agent-type that is free to reveal its preferences through decisions about pension system participation. Thus, we show that in Chile the appropriate focus for policy makers interested in the welfare-enhancing effects of such participation are the self employed. They are indistinguishable from other economically active agents with respect to time and risk preferences and sort into participants and non-participants in the pension system with reference to those preferences. In contrast, employees are rationed. The more patient and less risk averse self employed participate.